Pengaruh Motivasi terhadap Perilaku Kerja Petani Karet di Desa Puain Kanan Kecamatan Tanta Kabupaten Tabalong - Azwar Saihani; Siti Izzatil Sa’ira (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to determine the effect of motivation on working behavior of rubber farmers, knowing the dominant motivation of rubber farmers, knowing the positive or negative relationship and the percentage of the influence of motivation on the working behavior of rubber farmers in the Puain Kanan Village, Tanta District, Tabalong Regency. The research method used is the case study method with data collection methods, namely the interview method. Data collection is carried out from May to August. The analysis used was qualitative analysis of rubber farmer's work behavior, power motivation, affiliate motivation and achievement motivation. Quantitative analysis uses multiple regression analysis with simultaneous testing, partial testing, correlation coefficient and coefficient of determination using SPSS 23 software for Windows. The results obtained showed that motivation influenced the working behavior of rubber farmers with Fcount 12, 470. Performance motivation variables were the biggest motivations that influenced the working behavior of rubber farmers with the highest tcount value of 3.005. Motivation of power, affiliation motivation and achievement motivation have a positive relationship to the working behavior of rubber farmers with a motivation variable contribution value of 51%.